Penanganan Pasien COVID-19 dengan Schizofrenia di Wilayah Kerja Puskesmas Trosobo (Laporan Kasus) - Nurdianto, Arif Rahman (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2021)
Background: Schizophrenia patients infected with COVID-19 have become a problem in handling COVID-19 at the Sidoarjo regency community health center. Selection of drugs and handling of patients with their environment requires a different approach from normal patients. Research on COVID-19 with schizophrenia patients is very limited. The COVID-19 pandemic makes patient services and access unlike before the pandemic and is very limited so that access to schizophrenia patients, both controlled and uncontrolled, is still lacking and the effectiveness of therapy in schizophrenia patients with COVID-19 also still needs much research. Objective: Conduct a comprehensive study on how to diagnose, pathogenesis, therapy, and rehabilitate schizophrenia patients with COVID-19 infection Case report: Schizophrenia patients who were confirmed with COVID-19 through rRT-PCR examination were isolated at home and treated with medical treatment to overcome existing complaints, then given an injection of short-acting anti-anxiety drugs followed by maintenance therapy. Patients are treated at home by the puskesmas by involving their families and communities until they recover. Discussion: Schizophrenia patients are at risk of being infected with COVID-19 due to cognitive and behavioral disorders. Schizophrenia patients infected with COVID-19 must be given medical therapy based on complaints or negative symptoms that arise such as psychotic disorders or complaints caused by COVID-19 infection. Chlorpromazine (CPZ) can reduce psychotic disorders and hallucinations in these patients. Haloperidol can reduce positive symptoms that arise in patients so that patients can be calmer. Clobazam acts as a Gamma Amino Butyric Acid (GABA) which can reduce anxiety and agitation. Citicoline helps increase blood flow and oxygen consumption in the brain so that negative symptoms can be suppressed. Psychotherapy, family, and environmental support are needed to reduce psychosocial problems that arise due to COVID-19. Conclusions: Therapy of schizophrenia patients with COVID-19 is adjusted to psychotic problems and complaints due to COVID-19. A family-based therapy approach is needed during the isolation period to post COVID-19 health care.